ANALYSIS OF LOW STUDENT LEARNING MOTIVATION DURING THE PANDEMIC - Nisa Aulia Luthfiyanto (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2024)
The research is motivated by the many problems that occur during learning during the pandemic, one of which is the low motivation of students to learn. This study aims to determine the causes of low student motivation during the pandemic. This study used descriptive qualitative method. Data collection techniques using observation techniques, interviews and literature study (library research). The results of the research and discussion in this study are discussing the factors of low learning motivation caused; 1) Lack of facilities and infrastructure; 2) Lack of parental supervision; 3) Lack of appreciation; 4) Excessive use of smartphones.